Relationship between body image and motivation in dancers - Faria, Beatriz (2022)
Considering the importance of understanding how dancers perceive their body image, it is important to analyse the relationships that are established with other factors, namely with the way dancers regulate their behaviour. Therefore, the purpose of this work was to analyse the relationship between the way dancers regulate their behaviour and their satisfaction with body image, including a comparison between adolescents and adults.